Combined 18F-AlF-NOTA-FAPI-04 and 18F-Fluorodeoxyglucose PET/CT in patients with eosinophilic gastroenteritis: a case report and literature review - Chen, Bo; Wu, Tong; Xie, Jinghui (Frontiers in Medicine, 2025)
Eosinophilic gastroenteritis (EGE) is a rare chronic inflammatory disorder characterized by eosinophilic infiltration of the gastrointestinal tract. We report the case of a 42-year-old previously healthy man who presented with gradually worsening abdominal pain and bloating for approximately 1 month. Initial laboratory tests showed elevated eosinophil counts, increased immunoglobulin E levels, and raised C-reactive protein. Enhanced CT revealed diffuse edema of the gastric wall, thickening of the gastric and duodenal walls, enlargement of the abdominal lymph nodes, and thickening of the peritoneum, which was suspected to be caused by malignant tumors. However, gastroscopic pathological examination and multiple ascites examinations showed no obvious malignant cells. To investigate the underlying cause, the combined 18F-AlF-NOTA-FAPI-04 (18F-FAPI) positron emission tomography/computed tomography (PET/CT) and 18F-Fluorodeoxyglucose (18F-FDG) PET/CT were performed. The pattern of increased radionuclide uptake in these mentioned lesions differs from that of malignant neoplasms. Then, EGE was confirmed by diagnostic peritoneal biopsy. This case highlights that PET/CT imaging combined with 18F-FAPI and 18F-FDG demonstrates potential utility in diagnosing EGE, particularly in distinguishing inflammatory processes from malignancies.